Strategi Pemerintah Kota Padang dalam Pengembangan Pantai Muaro Lasak Sebagai Ikon Parawisata - Reymon Suri Putra; M. Fachri Adnan (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
This research aimed to analyze the strategy of Padang City Government in developing the Muaro Lasak beach as tourism icons. This was a qualitative research with descriptive qualitative method. Informants of this research were determined with purposive sampling, that was Tourism and Culture Department of Padang City, Public Works and Public Housing Services of Padang City, the tourists, traders, and parking attendants on the Muaro Lasak beach. This research used primary and secondary data derived from observation, interview, and documentation study. Validity tested of this data used source triangulation technique, and than the data were analyzed with qualitative data technique. The results of the research showed that neeed increased supervision, security and development in the strategy of Padang City Government in developing the Muaro Lasak beach as tourism icons. In addition, there are supporting factors and inhibiting factors in this case.